Changes in food consumption in an indigenous community in southern Belize, 1979-2019. (1st January 2022) - Cleary, Patrick; Mercer, Kristin; Usher, Kareem; Wilk, Richard; Wainwright, Joel
ABSTRACT: In recent years, scholars have studied the complex social and economic transformations of Belizean Maya livelihoods resulting from the historical legacies of British and Spanish colonization and the consolidation of capitalist social relations. However, little research has considered how the pathways through which indigenous Maya households procure food are being transformed. This paper examines changes in indigenous livelihoods over time, drawing upon results of household food surveys in Aguacate, Belize, from 1979 and 2019, and interviews with villagers about changes in the food system. We hypothesized that the principal changes would be an increased consumption of purchased food, a decrease in the percentage of maize in the diet, an increase in the consumption of meat, and an increase in food produced in agricultural monocultures (or outside of the milpa). Fieldwork supported these hypotheses. We found a decrease in the frequency of the household daily consumption of corn, and an increase in the frequency of daily wheat flour, rice, and chicken consumption. Interviewees tended to emphasize the last of these changes, blaming the growing consumption of store-bought chicken for perceived negative changes in village health. Several community members tied these changes to other broader transformations of the political economy.